1993
DOI: 10.3989/tp.1993.v50.i0.497
|View full text |Cite
|
Sign up to set email alerts
|

Espacio y metalurgia en la cultura castreña: la zona arqueológica de Las Médulas

Abstract: RESUMEN RESUMÉEL'anayse spatiale de produclion métallurgique de deux castros préromains astures nous permel de déterminer la présence d'un artisanat métallurgique a plein lemps, qui agit comme le fournisseur de la communauté des une «unité d'occupation ». JI est égalment possible de determ iner sa position sociale et le niveau de developpement technologique, ainsi que le cadre de sa production. Les possibilités d'approvisionnement de matiere premiere et les phenomenes interactifs dans le cadre de la Cultura Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…The use of crucibles rather than furnaces for the production of copper and copper alloys in low intensity, settlement-based production settings seems the norm rather than the exception in Iberia from the Chalcolithic right through to the Iron Age (Maya González et al, 1993, Gómez Ramos, 1999, Diaz et al, 2001, Figueiredo et al, 2010, Valério et al, 2013; especially at sites far from the Mediterranean influence, smelting crucibles were in use up to Roman times (Fernández-Posse et al, 1993, Rovira andMontero-Ruiz, 2013: 234). There is a rather convincing explanation for this technological tradition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of crucibles rather than furnaces for the production of copper and copper alloys in low intensity, settlement-based production settings seems the norm rather than the exception in Iberia from the Chalcolithic right through to the Iron Age (Maya González et al, 1993, Gómez Ramos, 1999, Diaz et al, 2001, Figueiredo et al, 2010, Valério et al, 2013; especially at sites far from the Mediterranean influence, smelting crucibles were in use up to Roman times (Fernández-Posse et al, 1993, Rovira andMontero-Ruiz, 2013: 234). There is a rather convincing explanation for this technological tradition.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting characteristic observed in Asturian castros, and which seems typical of the Iron Age in NW Iberia, is that the metallurgy of copper and iron was carried out in the same workshop and, possibly, by the same artisans (Fernández-Posse et al, 1993;Rovira and Gómez Ramos, 2001;Fanjul Peraza and Marín Suárez, 2006). In El Castru, fragments of iron objects were recovered alongside the crucible remains (González Álvarez, 2016).…”
Section: Excavations At El Castru In Vigañamentioning
confidence: 99%
See 1 more Smart Citation
“…Archaeological and geological research has been carried out in Las Médulas over the past few years yielding a wealth of information on many aspects on the dynamics of human-environment interactions during both the Iron Age and the Roman period (Fernández-Posse et al 1993;Orejas 1996;Fernández-Posse 1998;Sánchez-Palencia et al 1998;Hascar et al 1999;Pérez-García et al 2000;Pagés et al 2001). Conversely, archaeobotanical issues had been little explored in previous works and Correspondence: Leonor Peñ a-Chocarro, G.I.…”
Section: Introductionmentioning
confidence: 97%
“…Copper and tin bronze production techniques: Iberia is different A key peculiarity of the Iberian archaeometallurgical record is that, from the beginning of extractive copper metallurgy in the Chalcolithic and until Roman times, crucible smelting is the predominant system. Some examples include the Chalcolithic (third millennium BC) crucible fragments from Almizaraque and Las Pilas (Rovira and Renzi 2017;Müller et al 2004;Murillo-Barroso et al 2017), the samples from several sites reported by Rovira (2007) and dated from the Early Bronze Age (EBA) (2300-1300 BC) to Roman times (first millennium AC onwards), as well as crucibles from the IA hillforts (eighth century BC until Roman times) of La Corona de Corporales, el Castrelín de San Juan de Paluezas and El Castru, among others (Farci et al 2017;Fernandez-Posse et al 1993). There is evidence for the deliberate production of these technical ceramics from the EBA, as shown in the presence of pouring spout and grip handles that are absent in other ceramics (Soriano and Escanilla 2016).…”
Section: Introductionmentioning
confidence: 99%